cis-Golgi proteins accumulate near the ER exit sites and act as the scaffold for Golgi regeneration after brefeldin A treatment in tobacco BY-2 cells - Ito, Yoko (The American Society for Cell Biology, 2012)
Particular cis-Golgi proteins accumulate in novel punctate structures close to ERES by BFA treatment in tobacco BY-2 cells. These structures reassemble first to form cis-Golgi after BFA removal, and the Golgi stacks regenerate in the cis-to-trans order. This indicates that the punctate structures act as the scaffold for Golgi regeneration.